TOXIC ROMANTIC RELATIONSHIP PORTRAYED IN AFTER WE COLLIDED NOVEL OF ANNA TODD - Kartosugondo, Susan; Winardi, Yohanes Kurniawan; Fadilah, Eka (Universitas Widya Kartika Surabaya, 2023)
This research aims to explore the signs of a toxic relationship in the novel